Cognitive dysfunction and quality of life during pollen season in children with seasonal allergic rhinitis - Papapostolou, Georgia (Pediatr Allergy Immunol, 2020)
BACKGROUND: Allergic rhinitis often gives rise to impaired quality of life and is believed to also affect cognitive function. We aimed to examine whether cognitive functions were impaired during grass pollen season in symptomatic allergic children and to relate the degree of impairment to quality of life and biomarkers related to stress and inflammation. METHODS: Forty‐three grass pollen‐allergic children (age 8‐17 years) with non‐satisfactory effect of medication (antihistamines and nasal steroids daily) during previous seasons were included. In addition, 26 matched non‐allergic children were included as controls. Both groups performed cognitive tests (CANTAB) and completed Quality of Life questionnaires outside and during the pollen season. Blood samples were collected and analyzed for stress and inflammatory biomarkers. Pollen level was measured daily. RESULTS: Impaired cognitive function was found in spatial working memory, where the allergic group made more errors compared to the non‐allergic group during pollen season, but not off‐season. No significant differences could be seen between the allergic group and the controls in the other tests investigating visual memory or attention. Quality of health questionnaires revealed more symptoms and impaired quality of life in allergic compared to non‐allergic children, and increased symptoms in allergic children were associated with longer reaction time for simple movement during pollen season. No differences in stress or inflammatory biomarkers could be found between the groups. CONCLUSION: Cognitive function was affected during pollen season in pollen‐allergic children, and the more symptoms the allergic children had, the longer the reaction time in the cognitive tests.